Estudo sobre a associação entre doença periodontal e doença cardiovascular aterosclerótica em população nipo-brasileira - Silva, Alexandre Cândido da [UNIFESP] (2006)
Periodontal disease (PD), the most prevalent oral infection, has been associated with systemic diseases. This could facilitate the bacterial dissemination into circulation and adhesion to vascular walls, favoring inflammatory response. It is speculated that such bacteria in arterial wall would accelerate atherosclerotic process. Studies investigating this relationship found contrasting results. This cross-sectional epidemiological study examined the association of PD and cardiovascular disease (CVD), adjusted for a number of variables (logistic regression), in a population at high cardiovascular risk, living in Bauru, SP. 1,146 Japanese-Brazilians aged 30 years underwent standardized questionnaires, physical examination, doppler of extremities, electrocardiogram (ECG) and oral glucose tolerance test. Diagnosis of PD was based on the community periodontal index, and CVD on the history, ankle-to-brachial pressure index and ECG. Higher prevalence of PD was found in women as compared to men (48.1% vs 40.4%, p=0.008). Stratifying according to the presence of CVD, subjects with this disease were older (63.0±12.6 vs 56.0±12.1 years, p<0.001), showed higher levels of mean blood pressure (101.1±17.5 vs 96.3±14.7 mmHg, p<0.001), post-challenge plasma glucose (194.0±52.9 vs 163.0±58.4 mg/dl, p<0.001), non-HDL cholesterol (169.0±38.4 vs 163.0±35.1 mg/dl, p=0.041) and higher frequencies of smoking (38.5% vs 29.6%, p=0,029) and PD (60.2% vs 41.8%, p<0.001). Subgroups did not differ concerning anthropometric data. In logistic regression analysis, smoking (p=0.006),age (p<0.001), mean blood pressure (p=0.024) and post-challenge plasma glucose (p=0.016) showed to be independently associated with CVD; waist circumference (p=0.077) and PD (p=0.079) reached only borderline significance. In a Japanese-Brazilian population at high cardiovascular risk, our findings confirmed the classical associations of CVD with age, smoking and elevated plasma glucose but not with PD, what could reinforce literature hypothesis of an etiopathogenetic relationship between these diseases. Methodological limitations should contribute to the lack of statistical significance. Ongoing studies may deepen the investigation on this relationship which could contribute to general and oral health promotion in this population.